A CHAPTER REVIEW: WRITING MATERIAL FOR ESOL (ENGLISH FOR SPEAKERS OF OTHER LANGUAGES): (The Routledge Handbook of Materials Development for Language Teaching-Routledge) - Mustaqimah Muh Tang; Muhajirah Idman; Andi Tarbiyah Hasan (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2023)
This article's objective is to review Chapter 23 of Naeema B.Hann’s script in book